EFL LECTURERS’ TECHNOSTRESS IN LOW HDI CONTEXTS: FACTORS, IMPACTS, COPING STRATEGIES, AND INTERRELATIONSHIPS [TECHNOSTRESS DOSEN DALAM KONTEKS HDI RENDAH: FAKTOR, DAMPAK, STRATEGI PENANGGULANGAN, DAN KETERKAITAN] - Muslimin, Afif Ikhwanul (Universitas Pelita Harapan, 2024)
Abstract This mixed-methods study investigates English as a Foreign Language (EFL) lecturers' technostress in low Human Development Index (HDI) contexts, aiming to identify contributing factors, impacts, and coping strategies. The data collection was done through quantitative surveys and qualitative interviews. Twenty-two participants from public and private universities in West Nusa Tenggara, Indonesia, were selected based on their willingness to participate and provided demographic information. The analysis reveals that factors such as techno-complexity, techno-insecurity, and techno-uncertainty significantly contribute to high levels of technostress among EFL lecturers in low HDI contexts. Despite the challenges posed by technostress, participants exhibit adaptive skills in employing coping strategies effectively. The study underscores the need for tailored support programs, such as Technology Professional Development, to enhance EFL lecturers' technological proficiency and well-being. These findings have theoretical implications for understanding technostress in educational settings and practical implications for developing strategies to alleviate technostress and improve teaching outcomes in low-resource contexts. Bahasa Indonesia Abstrak Penelitian dengan metode campuran ini menyelidiki technostress dosen Bahasa Inggris sebagai Penutur Asing (EFL) dalam konteks Indeks Pembangunan Manusia (IPM) yang rendah, yang bertujuan untuk mengidentifikasi faktor penyebab, dampak, dan strategi penanggulangan. Pengumpulan data dilakukan melalui survei kuantitatif dan wawancara kualitatif. Dua puluh dua partisipan dari universitas negeri dan swasta di Nusa Tenggara Barat, Indonesia, dipilih berdasarkan kesediaan mereka untuk berpartisipasi dan memberikan informasi demografis. Analisis menunjukkan bahwa faktor-faktor seperti kompleksitas teknologi, ketidakamanan teknologi, dan ketidakpastian teknologi secara signifikan berkontribusi pada tingginya tingkat stres teknologi di kalangan dosen EFL dalam konteks IPM yang rendah. Terlepas dari tantangan yang ditimbulkan oleh technostress, para peserta menunjukkan keterampilan adaptif dalam menggunakan strategi mengatasi masalah secara efektif. Studi ini menggarisbawahi perlunya program dukungan yang disesuaikan, seperti pengembangan profesionalisme dalam penggunaan teknologi, untuk meningkatkan kemahiran dan kapabilitas dosen EFL. Temuan ini memiliki implikasi teoritis untuk memahami technostress dalam lingkungan pendidikan dan implikasi praktis untuk mengembangkan strategi untuk mengurangi technostress dan meningkatkan hasil pengajaran dalam konteks sumber daya rendah.